LOW TEMPERATURE BA-2270/U BATTERIES. - Soltis ,D. G.; Zeitz,E. J. (1962)
The BA-2270/U battery in the Cathodic Envelope construction gives an actual initial low temperature service level equivalent to 4 times that obtained under other contracts using conventional constructions. Increased electrode area and more intimate contact between materials of construction over the entire operating temperature range have been the prime factors giving this higher service level. High electrolyte solution volumes, higher concentrations of active ore and positive sealing of cells have also contributed to the service advantage. (Author)